2013
DOI: 10.1371/journal.pone.0053829
|View full text |Cite
|
Sign up to set email alerts
|

PhoB Regulates the Survival of Bacteroides fragilis in Peritoneal Abscesses

Abstract: In response to phosphate limitation, bacteria employ the Pho regulon, a specific regulatory network for phosphate acquisition. The two-component signal transduction system of PhoRB plays a crucial role in the induction of Pho regulon genes, leading to the adaptation to phosphate starvation. Herein, we identified the PhoRB system in Bacteroides fragilis, a commensal gut bacterium, and evaluated its role in gut colonization and survival in peritoneal abscesses. BF1575 and BF1576 encoded PhoR (sensor histidine ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…This observation indicates that inappropriate Pho activation is detrimental to bacterial pathogenesis. Other studies demonstrate that disruption of PhoPR can also be detrimental to bacterial virulence (12,(22)(23)(24)(25), including our observation that PhoPR is necessary for wild-type levels of staphylococcal pathogenesis. Notably, in this work, we observe that ΔphoPR and ΔpstSCAB ΔnptA mutants are similarly attenuated in the liver.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…This observation indicates that inappropriate Pho activation is detrimental to bacterial pathogenesis. Other studies demonstrate that disruption of PhoPR can also be detrimental to bacterial virulence (12,(22)(23)(24)(25), including our observation that PhoPR is necessary for wild-type levels of staphylococcal pathogenesis. Notably, in this work, we observe that ΔphoPR and ΔpstSCAB ΔnptA mutants are similarly attenuated in the liver.…”
Section: Discussionsupporting
confidence: 64%
“…PhoPR is important for virulence of S. aureus independent of P i transporter regulation. In several bacterial pathogens, PhoPR has a critical role in virulence (12,(22)(23)(24)(25). Additionally, phosphate metabolism has been linked to antibiotic resistance (46); specifically, a point mutation in pitA increases stationary-phase tolerance of S. aureus to the clinically important antibiotic daptomycin (DAP) (47).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…86 Under these Pi-limiting conditions, it has been shown that in Bacteroides fragilis PhoB was necessary for successful infection and survival in peritoneal abscesses. 87 In this study, activation of the Pho regulon induced a shift of B. fragilis from gut symbiosis to pathogenicity. Recently, it has been shown that Mycobacterium tuberculosis requires the Pst system to negatively regulate activity of RegX3 (a PhoB analog) in response to in vivo available Pi.…”
Section: Pho Regulon Expression During Infection and Immune System Himentioning
confidence: 62%